Micellar Enhanced Spectrofluorimetric Quantification of Gemifloxacin Mesylate in Pharmaceuticals and Bio-fluids - Al-Tamimi, Salma Ali; Al-Mohaimeed, Amal Mohammed; Alarfaj, Nawal Ahmad; Aly, Fatma Ahmed (Indian Journal of Pharmaceutical Education and Research)
Introduction: Gemifloxacin mesylate (GFX) is one of the most potential anti-infective agents with broad spectrum and influential activity. Objectives: The current study described a fast and precise spectrofluorometric probe for GFX quantification in authentic drug, commercial tablets and bio-samples. Materials and Methods: The suggested technique was conducted by complexing GFX with Al ions in the presence of alkaline buffer of pH 8. Results: The FI was enhanced by adding sodium dodecyl sulfate (SDS). Rectilinear relationship was achieved over (0.05-100 ng mL-1) drug samples. The fluorescence spectra were recorded at λex at 268 nm and λem 400 nm. The lowest quantification and detection values were 0.049 ng mL-1 and 0.05-100 ng mL-1, respectively. The suggested probe was employed to determine the investigated drug in its Factive® tablets with percentage recovery 99.85±0.7 %. In addition, the selected drug was also quantified in human serum and urine with percentage recovery 99.4 %. The outcome data were statistically treated and validated. Conclusion: The obtained results confirmed the suitability of this probe for the quantification of the drug in bio-fluids and commercial tablets.
Keywords: Complexation; Gemifloxacin mesylate; Spectrofluorimetry; Pharmaceutical; formulations; Bio-samples